The neomyth about the Lucifer in the V. Archer novel "Chose the abyss" - Калениченко, Ольга Николаевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article discusses a fantasy novel by V. Archer "Chose the abyss" in terms of the creation of the author of the neomyth about hell / the devil. On the one hand, the novel fits into the paradigm of modern Russian, American and European works of evil spirits, on the other – stands out for its attraction to serious ontological problems that has allowed to reveal the traditions of the Russian classical literature (the problem of the nature of man, his possibilities and moral choice, the plot of "enlightenment", etc.) and innovation associated with the original interpretation of the famous myth of Lucifer.